1998
DOI: 10.1098/rspb.1998.0405
|View full text |Cite
|
Sign up to set email alerts
|

Melanin–based plumage coloration in the house finch is unaffected by coccidial infection

Abstract: For most species of birds, ornamental plumage coloration may result from two types of pigments: carotenoids and melanins. Despite the fact that melanin pigments can be synthesized by birds from basic, amino acid precursors, while carotenoids cannot be synthesized by birds and must be ingested, melanin-based plumage coloration and carotenoid-based plumage coloration have often been treated as a single trait in investigations of the function and evolution of plumage coloration. Expression of carotenoid-based col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
107
3
2

Year Published

1999
1999
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(118 citation statements)
references
References 37 publications
6
107
3
2
Order By: Relevance
“…We do not consider our results are biased by the method used to estimate plumage colour because yellow coloration is largely lacking in emission in the ultraviolet portion of the spectra (Goodwin 1973;Gross 1987;Moss & Weeden 1999). Hue has normally been the parameter of interest when studying the relationship between plumage coloration and sexual selection (Hill et al 1994;Hill 1995;Hill & Brawner 1998;Nolan et al 1998;Wolfenbarger 1999), and hence it was initially the focus of our investigation. However, because colour intensity and lightness have also sometimes been found to have a degree of predictive value (Hill & Brawner 1998;Figuerola et al 1999a), we also explored the relationship of these two variables to parental investment.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We do not consider our results are biased by the method used to estimate plumage colour because yellow coloration is largely lacking in emission in the ultraviolet portion of the spectra (Goodwin 1973;Gross 1987;Moss & Weeden 1999). Hue has normally been the parameter of interest when studying the relationship between plumage coloration and sexual selection (Hill et al 1994;Hill 1995;Hill & Brawner 1998;Nolan et al 1998;Wolfenbarger 1999), and hence it was initially the focus of our investigation. However, because colour intensity and lightness have also sometimes been found to have a degree of predictive value (Hill & Brawner 1998;Figuerola et al 1999a), we also explored the relationship of these two variables to parental investment.…”
Section: Methodsmentioning
confidence: 99%
“…Secondary sexual coloration can be mainly categorized as structural or based on pigments such as carotenoids or melanin (Hill & Brawner 1998). In contrast to other kinds of coloration, carotenoids can only be obtained indirectly by animals through the food chain; as a consequence, it has been suggested that this coloration might serve as an honest signal of foraging (Endler 1980;Hill 1991;Gray 1996;Olson & Owens 1998;Grether et al 1999) and, hence, provisioning ability (Hill 1999).…”
Section: Introductionmentioning
confidence: 99%
“…In another study using house finches, Hill & Brawner (1998) investigated the effect of parasitism on carotenoid coloration. They found that juvenile males experimentally infected with a modest level of coccidians (Isospora species and/or Mycoplasma gallicepticum) developed plumage that was less red and had less saturated carotenoid coloration than juveniles treated that had sub-clinical infections.…”
Section: (D ) Wolf Spidersmentioning
confidence: 99%
“…In addition, previous experimental studies using parasites have found that (i) controlled infections reduce the expression of carotenoid-based ornamentation (Hill & Brawner 1998;Brawner et al 2000;Horak et al 2004), (ii) parasite eradication positively affects carotenoidbased ornamentation (Martinez-Padilla et al 2007), and (iii) expression level of ornaments may indicate males' ability to clear parasite infection (Lindströ m & Lundström 2000). Furthermore, newly developed methods, which allow measurement of the magnitude of the immune response to various antigens (see Adamo (2004) for a review), made it possible to identify a positive relationship between carotenoid-based coloration and various immune effectors (Blount et al 2003;McGraw & Ardia 2003 and references therein), and have also shown that immune defence and sexual attractiveness are constrained by carotenoid availability (Blount et al 2003;Grether et al 2004;McGraw & Ardia 2004).…”
Section: Introductionmentioning
confidence: 99%